Investigation of association rs266729 G/C ADIPOQ gene polymorphism with type two diabetes mellitus risk in Turkish population - Ulu, Ramazan; Dalkilic, Semih; Gozel, Nevzat; Kilinc, Faruk; Dogukan, Ayhan (Mattioli 1885, 2018)
One of the most important health problem is the diabetes in our century. There are some specific risk factors for diabetes for example genetic factors, obesity, immobility and life style. Some risk factors can be change but some of them unchangeable like genetic factors. Detection of plasma levels of some hormones and proteins can be useful. One of the important hormone which is the very useful predictor of early detection of diabetes is adiponectin. ADIPOQ gene contains 3 exons and 2 introns sequence, specifically promoter region is highly polimorphic and two important SNPs were identified. These SNPs are rs17360539 and rs266729 and it was determined that this two SNPs is very important for the association with risk of type 2 diabetes mellitus. In this study, we have investigated whether rs266729 ADIPOQ gene polymorphism is associated with risk of type 2 diabetes mellitus in Turkish population. In this study we have collected peripheral blood samples from 50 type 2 diabetes mellitus patients and 50 healthy control individuals. Genomic DNA was isolated from blood samples and ADIPOQ gene polymorphism was investigated by polymerase chain reaction restriction fragment length polymorphism assay (PCR-RFLP). In our results, we have not observed any statistically significant association between ADIPOQ gene polymorphism and risk of T2DM.
Keywords: type two diabetes mellitus; ADIPOQ gene; polymorphism